1996
DOI: 10.1103/physrevlett.76.3328
|View full text |Cite
|
Sign up to set email alerts
|

Ion Acceleration and Direct Ion Heating in Three-Component Magnetic Reconnection

Abstract: Portions of this document may be illegible in electronic image products. Images are produced from the best available original document. Ion acceleration and direct ion heating in three-component magnetic reconnection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
171
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(177 citation statements)
references
References 15 publications
6
171
0
Order By: Relevance
“…In the pioneering UCLA experiments, ion acceleration, possibly reduced by wave turbulence [7], and electron heating [8] were observed. However, ion heating could not be addressed because these experiments were in the "electron MHD" regime in which ρ i L. In TS-3 at the University of Tokyo, toroidal Alfvénic flows were believed to be accelerated by a "slingshot effect" of reconnected field lines, and global ion heating was attributed to thermalization of the sheared Alfvénic flows [9]. In SSX (Swarthmore Spheromak Experiment), Alfvénic ion jets correlated with reconnection were reported based on measurements of ion flux at the vacuum wall [10].…”
mentioning
confidence: 99%
“…In the pioneering UCLA experiments, ion acceleration, possibly reduced by wave turbulence [7], and electron heating [8] were observed. However, ion heating could not be addressed because these experiments were in the "electron MHD" regime in which ρ i L. In TS-3 at the University of Tokyo, toroidal Alfvénic flows were believed to be accelerated by a "slingshot effect" of reconnected field lines, and global ion heating was attributed to thermalization of the sheared Alfvénic flows [9]. In SSX (Swarthmore Spheromak Experiment), Alfvénic ion jets correlated with reconnection were reported based on measurements of ion flux at the vacuum wall [10].…”
mentioning
confidence: 99%
“…Gekelman & Stenzel (1985) also studied the anisotropy of the electron distribution in the reconnection layer using a novel electrostatic electron energy analyzer and found an energetic electron tail along the X-line. Ono et al (1996) observed ion outflow up to the Alfvén speed by Doppler shifts of impurity lines in an MHD plasma. Measurements were made with a polychrometer along a chord that could be scanned radially.…”
Section: /2 V P B/ (4pr)mentioning
confidence: 99%
“…Several laboratory experiments have measured energetic particles in reconnection geometries, but the emphasis has been on sub-Alfvénic outflow in the two-dimensional plane (Kornack, Sollins, & Brown 1998;Gekelman, Stenzel, & Wild 1982;Ono et al 1996). We previously observed an Alfvénic ion jet correlated with a reconnection event measured with a onedimensional probe .…”
Section: /2 V P B/ (4pr)mentioning
confidence: 99%
“…Since 1986 the merging of two toroidal plasmas (flux tubes) has been studied in a number of experiments: TS-3 [6] [7], START [8], MRX [9], SSX [10], VTF [11], TS-4 [12], UTST [13] [14], and MAST [15]. For those laboratory experiments, evidence of plasma acceleration toward outflow direction were observed as split line-integrated distribution function in 0D [16], 1D and 2D bidirectional toroidal acceleration during counter helicity spheromak merging [17] [18], and in-plane Mach probe measurement around X point with and without guide field [19][20] [21]. In the recent TS-3 experiment, with upgrade of diagnostics [22], 2D ion and electron heating characteristics are revealed [23] as bulk heating of ions at the downstream region and localized small electron heating around X point.…”
mentioning
confidence: 99%